Improving Students' Collaboration Skills Using the RADEC Learning Model in Elementary School Science Learning - Kiska, Nurul Delima; Haryanto, Eddy; Indryani, Indryani (Jurnal Pijar Mipa, 2024)
The learning model has an influence on the success of achieving learning objectives. One of the learning models that can improve the skills of students is the RADEC learning model. The syntax contained in the RADEC learning model can help learner-centered learning, namely Read, Answer, Discuss, Explain and Create (RADEC). Currently, collaboration is one of the learning activities that is very popular with students, where currently collaboration skills are found in the 4C skills of the 21st century, however, there are still many students who are still passive in collaborative learning activities. Science and Technology is one of the lessons in the current independent curriculum. This research aims to improve collaboration skills in students using the RADEC learning model. This research uses a classroom action research (PTK) model which is carried out in two cycles consisting of four stages starting from planning, action, observation and reflection. The implementation of learning in this research was carried out using the syntax contained in the RADEC learning model. The selection of research subjects was carried out through purposive sampling techniques and the research subjects in this study were class IV B students with a total of 32 students. Data collection techniques in research are observation and interviews. The results of this research showed an increase from the implementation of cycle I, namely at meeting one and meeting 2 there was an increase of 6.6% and in cycle 2 at meeting 1 and meeting 2 there was an increase of 13.34%. Based on the results of this research, it can be seen that implementing learning using the RADEC learning model can improve students' collaboration skills in science learning. Based on the research that has been done, it can be said that the RADEC learning model can improve student collaboration skills in the learning process which is marked by the fulfillment of collaboration skill indicators by students.